The effects of hospital clowning on physical and emotional states of pediatric patients during chemotherapy treatment - Arriaga, P. (2020)
Background: Pediatric cancer treatments interfere with the patient’s life on physical, psychological, and social levels. Hospital Clowns (HCs) use nonpharmacological techniques to reduce the distress that hospital treatments can cause and increase children’s wellbeing, but few studies have analyzed their effects. Objective: This study examined the HC effects on the physical and emotional responses of pediatric patients during ambulatory chemotherapy. Given the variability in patients’ adjustments to cancer treatment, the role of a child’s age and temperament, and caregiver anxiety was considered in explaining the responses over and beyond the HC effects on patient outcomes. Method: Following a quasi-experimental design, 82 pediatric patients were assigned to one of two conditions: HC intervention versus control group (CG) in two separate trials. Pediatric patients self-reported of physical symptoms (pain, nausea, and fatigue) and emotional states (distress, happiness, and calm) were measured at baseline and post-chemotherapy in both trials. Caregivers provided information on children’s temperament and reported their own anxiety. Marginal Multilevel Modeling was used to examine the effects of the HC interventions on the outcomes by controlling caregiver anxiety, and child age and emotionality. Results: Compared to the CG, patients receiving the HC visit during chemotherapy reported higher levels of calm and happiness, and less fatigue, pain, and distress. HCs did not affect nausea. Conclusions: This study showed the importance of HCs as agents of supportive pediatric care, whose short-term effects during ambulatory chemotherapy seem to contribute to increasing the well-being of pediatric patients.